ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATI DAN KESALAHAN MENYELESAIKAN SOAL CERITA MENGGUNAKAN PROSEDUR NEWMAN - Tahir Tahir; Marniati Marniati (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This research is a descriptive study, which aims to see the ability of students' conceptual understanding and errors made in solving story problems on fractional material using the Newman procedure. The subjects of this research were the fifth grade students in SD Negeri in Lalolae totaling 54 students. The instrument used in this study was an essay test which was developed and tested for feasibility. From the results of the research, from 54 students of the research subjects, the average value of students' conceptual understanding ability was 41.48 or in the low category. From the results of the categorization of students' conceptual understanding abilities, the majority of the students have concept understanding abilities in the low and very low categories with 74% in total. Furthermore, from the results of student error analysis using the Newman procedure, the students made 215 errors and the most errors made by students were Comprehension errors